Smoking and nicotine in inflammatory bowel disease: good or bad for cytokines? - F. J. Zijlstra (Mediators of Inflammation)
Smoking has either a beneficial or harmful effect on the course and recurrence of ulcerative colitis and Crohn's disease respectively. Transdermal application of nicotine had similar effects in ulcerative colitis and therefore was considered to be an effective basic drug which could be further developed in the search for new compounds in the treatment of acute exacerbations of corticosteroid resistant ulcerative colitis. In this communication the short-term use of nicotine in ulcerative colitis is reviewed.